Phillyrin Attenuates Osteoclast Formation and Function and Prevents LPS-Induced Osteolysis in Mice - Wang, Jing; Chen, Gang; Zhang, Qianqian; Zhao, Fuli; Yu, Xiaolu; Ma, Xuemei; Liu, Mei (Frontiers in Pharmacology, 2019)
As the sole cell type responsible for bone resorption, osteoclasts play a pivotal role in a variety of lytic bone diseases. Suppression of osteoclast formation and activation has been proposed as an effective protective therapy for new bone. In this study, we reported for the first time that phillyrin (Phil), an active ingredient extracted from forsythia, significantly and dose-dependently inhibited RANKL-induced osteoclastogenesis and bone resorption. Phil also significantly suppressed RANKL-induced transcript levels of osteoclast-specific genes including cathepsin K (CTSK), tartrate resistant acid phosphatase (TRAP) and calcitonin receptor (CTR). Further molecular investigation demonstrated that Phil effectively blocked RANKL-induced activations of JNK and ERK which suppressed the expression of NFATc1 and c-fos. Taken together, these data suggested that Phil might be a potential anti-osteoclastogenesis agent for treating osteoclast-related diseases.